Enantioselective Tissue Distribution of Ketorolac and its Enantiomers in Rats - Dubey, S. K.; Anand, A.; Saha, R. N. (Drug Research, 2015)
The difference in tissue distribution of Ketorolac and its enantiomers were investigated in wistar rats. Separate high performance liquid chromatographic method was developed and validated for determination of Ketorolac and its enantiomers. Oyster BDS (150×4.6 mm id., 5 μm particle size) column was used for determination of concentration of Ketorolac. Ketorolac enantiomers were determined using Chiral-AGP column (100×4.0 mm I.D., particle size 5 μ, Chrom tech Ltd, Sweden). Detection was done at wavelength of 322 nm using an ultraviolet detector in the analytical system. Ketorolac enantiomers exhibit difference in their disposition in Wistar rats. In kidney, there was a significant difference in pharmacokinetic parameters. The Cmax was nearly 4 times and AUC0–∞ was found to be more than double for S (−) Ketorolac than that of R (+) Ketorolac. MRT, Ke and t1/2 differ significantly in kidney. In liver, Cmax was found to be approximately 69% higher for S (−) Ketorolac compared to R (+) Ketorolac. AUC0–∞ did not differ significantly for the enantiomers in liver. In liver, S (−) Ketorolac eliminated very fast in comparison to R (+) Ketorolac having t1/2 (one third) in comparison to R (+) Ketorolac. In lungs, there was no difference observed for Cmax and other parameters but AUC0–∞ was found to be marginally higher for S (−) ketorolac.
Keywords: ketorolac; enantiomers; pharmacokinetics; tissue distribution